Numerical Study of Influences of Onshore Wind on Hydrodynamic Processes of Solitary Wave over Fringing Reef - L. Guo; K. Qu; J. X. Huang; X. H. Li (Journal of Marine Science and Engineering, 2022)
Many post-disaster surveys have reported on the natural function and effectiveness of fringing reef in preventing the shoreline from the inundation caused by severe weather events. Prior studies mainly focus on the wave propagating, transforming, and breaking on the fringing reefs by assuming that ocean waves propagate in an ideal environment where the wind is absent. However, in the real severe ocean environment, huge surges and waves always occur simultaneously with the strong winds. The wave profile can be easily reshaped by the strong winds, which can also significantly affect the way that ocean waves propagate on the fringing reefs. Therefore, it is necessary to study the hydrodynamics of fringing reefs under the combined action of wind and waves. To study the influences of the onshore wind on the hydrodynamics of solitary wave on the fringing reef, the finite volume method is applied to solve the governing equations of two-phase incompressible flow and a high-resolution numerical wind-wave tank is established in this study. Effects of several main factors are analyzed in detail. The research results show that the onshore wind can significantly increase the maximum wave runup height (maximum by 38.49%) and decrease the wave reflection coefficient of solitary wave (maximum by 8.66%). It is hoped that the research results of this study can enhance the understandings on the hydrodynamics of ocean waves on the fringing reefs during severe weather events.